Effects of probiotic Lactobacillus gasseri strains of breast-fed infant in a murine model - Ramos, Maria da Penha Piccolo; Pancoto, João Alexandre Trés; Carlos, Iracilda Zeppone [UNESP]; Almeida, Rogeria Comastri de Castro; Maia, Danielle Cardoso Geraldo [UNESP]; Ribeiro, Lívia Carolina de Abreu [UNESP]; Benzatti, Fernanda Paulin [UNESP]; Cunha, Luciana Rodrigues; Silva, Aline Costa e; Ferreira, Célia Lucia de Luces Fortes (My University, 2015)
The ingestion of probiotic lactic acid bacteria has been evaluated and noted that it has an effect on the balance of desirable microbiota in the gastrointestinal tract. Lactobacillus gasseri demonstrates good survival in the gastrointestinal tract, and it has been associated with a variety of probiotic activities and roles, including the reduction of fecal mutagenic enzymes, the production of bacteriocins and the stimulation of macrophages immunomodulation. The aim of the study was to evaluate the effects of a pool of L. gasseri strains isolated from the feces of breastfed infants added in the human milk of healthy women. The milk was both pasteurized and unpasteurized, to verify the cell cytotoxicity of macrophages and to quantify the production of immunologic mediators such as IL-4, IL-6, IFN-g, TNF-a, NO and oxygen intermediary compounds (H2O2). The administration of raw human milk and pasteurized human milk to infants is a regular, encouraged practice in units of intensive therapy (UITs) and our present investigation verified the beneficial effect of addition of a pool of L. gasseri to pasteurized human milk (PHML). Our results show that probiotic supplementation helped to maintain cell viability, reduced IL-6 and IFN-γ production and stimulated TNF-α, NO, H2O2, IL-4 production. Nevertheless, the results indicate that the addition of lactobacillus to human milk was not a determinant in the production of TNF-α. L. gasseri added to breast milk did not present a cytotoxic risk, and the addition of L. gasseri to pasteurized milk of human milk bank would benefit newborns that depend on milk banks for the colonization of more desirable microbiota.
Keywords: Probiotic; Human milk bank; Immunology; Lactobacillus gasseri